Applicability of ELISA with different antigens to diagnose varying levels bovine cysticercosis - Silva, Letícia Ferreira; Pinto, Paulo Sérgio Arruda; Duarte, Camilla Taveira Ducas; Santos, Tatiane de Oliveira; Nieto, Emílio Campos Acevedo; Peixoto, Rafaella Paola Meneguete dos Guimarães (Semina: Ciências Agrárias, 2015)
The efficiency of larval Taenia crassiceps (Tcra) antigens was evaluated by enzyme-linked immunosorbent assay (ELISA) to diagnose bovine cysticercosis. Three types of antigens were evaluated: total (T), total sonicated (Ts), and membrane (M); these samples included positive and negative control sera for cysticercosis, as well as sera for other pathologies. The sensitivity rates of ELISA were determined to be 85.0 and 81.25% for T antigen, 82.5 and 78.75% for Ts antigen, and 80.0 and 80.0% for M antigen, using cut-off points with standard deviations (SD) of 2 and 3, respectively; the specificity rates of ELISA were 47.5 and 58.75% for T antigen, 65.0 and 73.75% for Ts antigen, and 58.75 and 62.5% for M antigen, using 2 and 3 SD cut-off points, respectively. These results demonstrated that ELISA, which displayed a better performance in the detection of experimentally infected animals, had a higher sensitivity than the anatomical and pathological examination performed (during routine post-mortem inspections) in other studies. However, the post-mortem investigation is highly specific, and the specificity was higher than that of ELISA. Therefore, a combination of these diagnostic tests must be utilized for the accurate detection of bovine cysticercosis, demonstrating the practical applicability of ELISA.

Ensaios foram conduzidos para avaliar a eficiência de antígenos de larva de Taenia crassiceps (Tcra) no teste ELISA para o diagnóstico da cisticercose bovina. Três antígenos foram avaliados: total (T), total sonicado (Ts) e de membrana (M). As amostras analisadas foram soros-controle positivos e negativos para a cisticercose, além de soros de bovinos com outras patologias. As taxas de sensibilidade para o teste ELISA foram respectivamente, com 2 e 3 desvios-padrão, 85,0 e 81,25% para o antígeno T, 82,5 e 78,75% para o antígeno Ts e 80,0 e 80,0% para o antígeno M; as taxas de especificidade, com 2 e 3 desvios-padrão, foram respectivamente: 47,5 e 58,75% para o antígeno T, 65,0 e 73,75% para o antígeno Ts e 58,75 e 62,5% para o antígeno M. Estes resultados demonstram que o ELISA, apesar de apresentar melhor desempenho em detectar animais experimentalmente infectados, apresentou taxa de sensibilidade superior ao exame anatomopatológico realizado durante a rotina de inspeção relatada por outros estudos. No entanto, o exame post mortem é superior quanto a especificidade, uma vez que é considerado altamente específico. Assim, a combinação de ambas as técnicas diagnósticas deve ser valorizada na detecção da cisticercose bovina, demonstrando a aplicabilidade prática do ELISA.
Keywords: Bovine cysticercosis; ELISA; Performance rates; Taenia crassiceps